Quantum oscillations of resistivity in bismuth nanowires - Condrea, E.; Gilewski, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We studied the influence of uniaxial deformation on the transport properties of bismuth wires in the wide range of temperatures. Measurements of the resistance of bismuth nanowires with several diameters and different quality reveal oscillations on the dependence of resistance under uniaxial strain at T = 4.2 K. Amplitude of oscillations is significant (38%) at helium temperature and becomes smearing at T = 77 K. Observed oscillations originate from quantum size effect. Evaluation of period of oscillations allows us to identify the groups of carriers involved in transport. Calculated periods of 42.2 and 25.9 nm satisfy approximatively the ratio 2:1 for two experimentally observed sets of oscillations from light and heavy electrons.